INVESTIGATION ON THE FREE RADICAL SCAVENGING ACTIVITY OF BIOGENIC SILVER NANOPARTICLE - SANGEETHA ARUN; SARASWATHI U; SINGARAVELU (International Journal of Pharma and Bio Sciences, 2015)
Nanomedicines are a recent offshoot of the application of nanotechnology to medical and pharmaceutical challenges. The advent of nanoparticles has opened up new avenues in many different fields. The biomedical properties of silver nanoparticles were premeditated as free radical scavenging activity. Mangrove Excoecaria agallocha synthesized silver nanoparticles serve as strong hydroxyl, superoxide, nitric oxide and DPPH radical scavenger.